Agenesis of third molars and its association with other dental anomalies in a Peruvian population. - Alberto Miranda-Medina (Universidad de Concepción., 2020)
Objective: The purpose of the present study was to determine the association between agenesis of the third molar and other dental anomalies. Materials and Methods: This was an observational, retrospective, cross-sectional and analytical study. The sample included 367 patients, aged 14 to 20 years old with adequate digital panoramic radiography. Patients with syndromes, who had extractions of any third molar and with orthodontic treatment prior to panoramic radiographic examination, were excluded. For data collection, each radiograph was recorded with patient code, sex and age. Results: The prevalence of third molar agenesis was 20.71%. Subsequently, patients were divided into two groups, with agenesis of at least one third molar and a control group; the prevalence of other dental anomalies was 48.69% of third molar agenesis group and 21.31% in the control group. A highly significant association was found between the presence of third molar agenesis and the presence of other tooth abnomalities (p= 0.0000; contingency coefficient = 0.2425).The most frequent dental anomaly was dental inclusion with 20.44% of the population studied; followed by the agenesis of other teeth (7.90%) and finally the presence of supernumerary teeth (1.63%). Conclusions: This study demonstrates that there is an association between third molar agenesis and other dental abnormalities, with a higher prevalence of dental abnormalities in patients with third molar agenesis.